PENGARUH INVESTASI DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PENDAPATAN ANTAR PROVINSI DI KALIMANTAN BARAT - Hasanah, Hasanah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
This study aims to determine the effect of investment and economic growth on income inequality in 5 Kalimantan Provinces, using Panel Data Regression Analysis. Based on the results of this test, it shows that from the results of the partial test, investment has a negative effect on income inequality, which shows that the high realization of this investment has proven effective in creating jobs for local residents where the workforce increases which has an impact on reducing people's income inequality and economic growth. has a positive effect on income inequality because in the early stages of economic growth, inequality tends to worsen, and in later stages, inequality will improve, but at one time there will be an increase in disparity again and finally decrease again. Therefore the Provincial Government in Kalimantan needs to improve a conducive investment climate by providing incentives for entrepreneurs to be interested in investing in the region, this form of incentive can be in the form of ease in establishing new businesses. Keywords: Invesment, Economic Growth, Income Inequality, Panel Data Regression